أنواع الوقف واستخداماته المحتملة في إندونيسيا [Types of waqf and its potential uses in Indonesia] - Muayyad, Deden Misbahudin; Tahir, Ibrahim Nuhu (Universitas Islam Indonesia, 2023)
This paper aims to explain the types of waqf and its applicability in Indonesia. This paper uses the descriptive theoretical approach by exploring the theory of the endowment and its types in Islam. The results of this paper are that the types of waqf are very diverse, the number of waqf assets is very large in Indonesia, and the large Muslim population is an opportunity to develop waqf in Indonesia in a more diverse way. The endowment includes the good endowment, the civil endowment, the joint endowment, the permanent endowment, the temporary endowment, the investment endowment, the direct endowment, the real estate endowment, the movable endowment, and the cash endowment. تهدف هذه الورقة إلى شرح أنواع الوقف وإمكانية تطبيقه في إندونيسيا. تستخدم هذه الورقة المنهج النظري الوصفي من خلال استكشاف نظرية الوقف وأنواعه في الإسلام. نتائج هذه الورقة هي أن أنواع الوقف متنوعة للغاية، وعدد أصول الوقف كبير جدًا في إندونيسيا، والعدد الكبير من السكان المسلمين هو فرصة لتطوير الوقف في إندونيسيا بطريقة أكثر تنوعًا. يشمل الوقف وقف الخير، ووقف الأهلي، والوقف المشترك، والوقف الدائم، والوقف المؤقت، والوقف الاستثماري، والوقف المباشر، والوقف العقاري، ووقف المنقولة، والوقف النقدي.